Discursive Analysis of Pediatrician's Therapeutic Approach towards Childhood Fever and Its Contextual Differences: An Ethnomethodological Study - Francisco Vicens-Blanes; Rosa Miró-Bonet; Jesús Molina-Mula (MDPI AG, 2024)
Introduction: Fever stands out as the predominant clinical indicator in infancy. Pediatricians encounter fever routinely in their daily practice, playing a crucial role in their interactions with children and families. Objective: The aim is to examine pediatricians' viewpoints, understanding, and approaches regarding childhood fever in two healthcare settings: pediatric hospitalization (emergency and inpatient ward) and primary care. Methods: A qualitative study was conducted using an ethnomethodological approach. Pediatricians working in the specified pediatric settings participated in in-depth interviews where theoretical clinical cases were presented for analysis. Results: Following the examination of the discourses, the codes were organized into eight categories: Understanding of fever, Significance ascribed to fever, Therapeutic strategies, Engagement with the evidence, Family apprehensions regarding fever, Influence of the COVID-19 Pandemic, Inter- and intra-professional relationships, and Suggestions for change: Conclusions: Pediatricians acknowledge the importance of addressing discomfort in the treatment of fever, but express challenges in implementing these recommendations. Pediatricians in inpatient settings emphasize the need for enhanced parental education from primary care, while those in primary care recognize the potential for improvement. Inpatient pediatricians are open to implementing changes in their daily practices, particularly concerning the administration of antipyretics.